Editorial Vol. 16 No. 22 - Saavedra, Jorge Humberto (Universidad Pedagógica y Tecnológica de Colombia, 2009)
The Faculty of Engineering of the Pedagogical and Technological University of Colombia considers it especially important to highlight the work of people who, with their management and attitude, have left a pleasant mark and contributed to the growth of Engineering and the training of new Engineers in our environment.